من وجوه البيان ودلالاتها البلاغية في المعلقات السبع : دراسة وصفية وتحليلية - Mohamed Haji Ibrahim (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
This study aims to object extraction statement in the famous poems in pre-Islamic era, known by Al-Mu'allaqat. The researcher will address the study of metaphor and simile, metaphor and metonymy, and extraction of these pendants, relying in this public on the analytical and descriptive method. The study entirely revolves around a single frame which is awareness of the statement. At this level, the extraction of artistic photography or artistic image of the verses, and then analyzed morally is considered an important issue to highlight the meanings. The researcher in the study, delves in which lies behind the graphic method, wrote annotations to learn the meanings of words and the overall meaning of Arabic sonnet, depending on Az-Zouzani book, Al-Khatib At-Tabrizi book, Al-Anbari book, and Ibn An-Nahhas book. The researcher chose seven suspensions of ten known, and pendants that have proven in the book to explain the seven pendants for Az-zouzni. These pendants are: Imru'o AlQais, Tarafa Ibn Al-Abd, Zuhair bin Abi Sulma, Labid bin Rabi'a, Amr Ibn Kulthum, Antara ibn Shaddad, Harith Bin Halzh. The researcher expects that the benefit of this research is for scholars in the field of rhetoric and literature, where it is easier for them to understand literary texts of ancient heritage, at the same time provides a clear approach in the analysis of rhetorical and artistic images of poems in pre-Islamic era.